THE INFLUENCE OF THINK PREDICT READ AND CONNECT STRATEGY TOWARDS STUDENTS’ READING ABILITY - IMAM SUBARI; TOMMY HASTOMO; MEGA TRI NOVANA (English Department, STKIP PGRI Bandar Lampung, 2022)
Many students in Senior High School cannot master reading ability it might be caused by the students’ inability of using dictionary, inability in comprehending the text and unfamiliarity of words. In overcoming this problem, the researcher tried to used of think predict read and conect strategy. In reading ability this strategy can help the students in comprehending the text easily. The objective of the research was to know the influence of of think predict read and conect strategy towards students’ reading ability. In this research the writer used experimental method. The population of this research was 281 students. The sample was taken by using Cluster Random Sampling technique. In data collecting technique the writer used test, the test was multiple choice, consisted of 40 items. Based on the result of the data analysis and computation which used the formula of ttest, the result of analysis the data is significant, which is ttest > ttab : 4.03 > 1.67. From the result of analysis data, the writer could to give some conclusions as 1).The average score of the students’ reading ability who were taught by think, predict, read, and connect strategy was higher than who were taught with conventional strategy. It was seen from average score of test on experimental class is higher than the average score of control class X1 = 76.2 > X2 = 67.78. 2).There is a significant influence of giving translation assignment towards students’ English reading ability. It was seen from the result of ttest > ttab : 4.03 > 1.67.